(untitled) (REMUNOM, 2025)
The proposal of teaching Brazilian Sign Language (Libras) to hearing individuals creates opportunities for a diverse and inclusive linguistic society. Therefore, the present research aimed to identify the impacts of teaching Libras to hearing students and students with hearing impairments in the context of elementary education. The investigation was conducted through systematic observation of the classes of the institutional project “Libras in Action – Introduction to Libras Teaching,” developed in a public school located in the outskirts of Linhares-ES, Brazil. Adopting a qualitative approach, the objectives focused on the methods used by the teachers and the effects of social interaction among the students, considering parameters such as lesson topics, resources used, applied activities, as well as the attitudes of the teachers, hearing students, and the student with a hearing impairment. These elements formed the basis for data analysis and discussion. The results indicate the relevance of formal education as a tool to ensure the inclusion of deaf and hearing-impaired individuals in society. Additionally, it highlights the need for pedagogical practices and projects that recognize Libras as a linguistic right and as a mediating tool for full participation in school and social life.